Non Susceptibility of Neonatal and Adult Rats against the Middle East Respiratory Syndrome Coronavirus - Iwata-Yoshikawa, Naoko; Fukushi, Shuetsu; Fukuma, Aiko; Suzuki, Tadaki; Takeda, Makoto; Tashiro, Masato; Hasegawa, Hideki; Nagata, Noriyo (Japanese Journal of Infectious Diseases, 2016)
The present study examined the susceptibility of rats to the Middle East respiratory syndrome coronavirus (MERS-CoV) and determined whether this animal is a suitable model for MERS-CoV infection. Immunohistochemical analysis identified dipeptidyl peptidase 4 (DPP4), a known receptor for MERS-CoV on type I pneumocytes from infected rats. Whereas adult rats developed antibodies against MERS-CoV spike protein after intranasal inoculation, there was no evidence of viral replication in the lungs of adult, young, or neonatal rats after intranasal inoculation with MERS-CoV. In addition, human DPP4-expressing rat kidney fibroblasts, but not rat DPP4-expressing cells, were susceptible to MERS-CoV. Taken together, these results suggest that the rat is not a useful animal model for studying MERS-CoV infection.